Biodegradable nanofiber bone-tissue scaffold as remotely-controlled and self-powering electrical stimulator. (October 2020) - Das, Ritopa; Curry, Eli J.; Le, Thinh T.; Awale, Guleid; Liu, Yang; Li, Shunyi; Contreras, Joemart; Bednarz, Casey; Millender, Jayla; Xin, Xiaonan; Rowe, David; Emadi, Sharareh; et al.
Abstract: Electrical stimulation (ES) has been shown to induce and enhance bone regeneration. By combining this treatment with tissue-engineering approaches (which rely on biomaterial scaffolds to construct artificial tissues), a replacement bone-graft with strong regenerative properties can be achieved while avoiding the use of potentially toxic levels of growth factors. Unfortunately, there is currently a lack of safe and effective methods to induce electrical cues directly on cells/tissues grown on the biomaterial scaffolds. Here, we present a novel bone regeneration method which hybridizes ES and tissue-engineering approaches by employing a biodegradable piezoelectric PLLA (Poly(L-lactic acid)) nanofiber scaffold which, together with externally-controlled ultrasound (US), can generate surface-charges to drive bone regeneration. We demonstrate that the approach of using the piezoelectric scaffold and US can enhance osteogenic differentiation of different stem cells in vitro, and induce bone growth in a critical-sized calvarial defect in vivo . The biodegradable piezoelectric scaffold with applied US could significantly impact the field of tissue engineering by offering a novel biodegradable, battery-free and remotely-controlled electrical stimulator . Graphical abstract: Image 1 Highlights: A biodegradable, battery-less electrical stimulator made of PLLA piezoelectric nanofibers, serves as a bone scaffold. Application of ultrasound on the cell-seeded nanofibers can enhance osteogenic differentiation of stem cells. This approach, using PLLA nanofibers and remotely-controlled ultrasound, induces healing in a skull bone defect in mice.